A unique case of traumatic pulmonary food embolism. (February 2020) - Lanzillotta, Fiorella; Visonà, Silvia Damiana; Ballardini, Marco; Javan, Gulnaz T.; Osculati, Antonio
Abstract: We report a unique case of post-traumatic pulmonary food embolism, due to a lethal blunt force trauma occurred in a traffic accident. The subject was a 37-year old man, victim of a road traffic accident while he was riding his motorbike. A forensic autopsy, followed by histological examination, was ordered in order to find out the cause of death and to assess the compatibility of the lesions with the dinamic of the accident. Autopsy revealed a blunt force thoraco-abdominal trauma responsible of the death. The most interesting histological evidences concerned lungs. Here, inside arterious and arteriolar pulmonary vessels, we identified crystal-like corpuscles, of various shape and size, sometimes aggregated in small masses and thin vegetal fibers, refracting at polarized light, both PAS-positive and meat fibers shadows. The presence of alimentary material in the pulmonary vessels was explained by a pulmonary food embolism. The occurring of this kind of embolism implies a communication between the viscera lumen and the venous circulation of his wall (through a small wall rupture) in presence of cardiocirculatory activity, and provides, therefore, a strong proof of vitality. Highlights: Pulmonary food embolism can occur as a consequence of traumas. The presence of food into pulmonary arterious vessels can be explained by pulmonary embolism. Microscopic detection of pulmonary food embolism is a valuable proof of vitality. Pulmonary food embolism can have a role in the determination of death.